Effects of Complex Training on Sprint, Jump, and Change of Direction Ability of Soccer Players: A Systematic Review and Meta-Analysis - Thapa, Rohit K.; Lum, Danny; Moran, Jason; Ramirez-Campillo, Rodrigo (Frontiers in Psychology, 2021)
The aim of this meta-analysis was to evaluate the effects of complex training (CT) on sprint, jump and change of direction (COD) ability among soccer players. After an electronic search, ten peer-reviewed articles were considered in the meta-analysis. The athletes included in this meta-analysis were amateur to professional level male soccer players (age range, 14 to 23 years). These studies incorporated CT in soccer players who were compared to a control group. Significant moderate to large improvements were observed in the CT group (sprint: standard mean difference [SMD] = 0.92 to 1.91; jump: SMD = 0.96 to 1.58; COD: SMD = 0.97 to 1.49) when compared to control groups. Subgroup analysis were also conducted based on age, duration, and competitive level. The beneficial effects of CT were greater in players <18 years vs ≥18 years (linear sprinting; SMD = 2.01 vs -0.13), after ≥8 weeks vs <8 weeks (jumping and COD; SMD = 1.55 to 2.01 vs 0.31 to 0.64, respectively) and among professional vs amateur players (linear sprinting and with COD; SMD = 1.53 to 1.58 vs 0.08 to 0.63, respectively). In conclusion, regular soccer training programs may be supplemented with CT to improve sprint, jump and COD performance. A longer duration of CT (≥8 weeks) seems to be optimal in improving the physical abilities of soccer players. Professional players and <18 years players may benefit more from CT program.